Humanity and Justice: Exploring Human Rights in the Context of Islamic Law - Karimullah, Suud Sarim (Research and Development Institution, Darussalam Institute for Islamic Studies, 2023)
This study explores the relationship between the concepts of humanity, human rights, and social justice in the context of Islamic law. Using the method of literature study and comprehensive literature analysis of the results of previous studies. This study aims to outline how Islamic law recognizes human dignity, protects individual rights, and promotes social justice. The results of this study reveal that Islamic law has a strong foundation in the principles of humanity, human rights, and social justice. Islamic law recognizes human dignity, integrates individual rights, and encourages the protection of the vulnerable. This concept creates a strong moral foundation for achieving a more just and inclusive society. In an increasingly connected and diverse world, a deep understanding of the relationship between Islamic law and Human Rights is key to promoting tolerance, mercy, and peace. With constant dialogue and thoughtful implementation efforts, Muslim societies can play an important role in building a better world that respects individual rights without forgetting the precious values of religion.